Global disability-adjusted life-year estimates of long-term health burden and undernutrition attributable to diarrhoeal diseases in children younger than 5 years. Issue 3 (March 2018) - Troeger, Christopher; Colombara, Danny V; Rao, Puja C; Khalil, Ibrahim A; Brown, Alexandria; Brewer, Thomas G; Guerrant, Richard L; Houpt, Eric R; Kotloff, Karen L; Misra, Kavita; Petri, William A; Platts-Mills, James; et al.
Summary: Background: Diarrhoea is a leading cause of death and illness globally among children younger than 5 years. Mortality and short-term morbidity cause substantial burden of disease but probably underestimate the true effect of diarrhoea on population health. This underestimation is because diarrhoeal diseases can negatively affect early childhood growth, probably through enteric dysfunction and impaired uptake of macronutrients and micronutrients. We attempt to quantify the long-term sequelae associated with childhood growth impairment due to diarrhoea. Methods: We used the Global Burden of Diseases, Injuries, and Risk Factors Study framework and leveraged existing estimates of diarrhoea incidence, childhood undernutrition, and infectious disease burden to estimate the effect of diarrhoeal diseases on physical growth, including weight and height, and subsequent disease among children younger than 5 years. The burden of diarrhoea was measured in disability-adjusted life-years (DALYs), a composite metric of mortality and morbidity. We hypothesised that diarrhoea is negatively associated with three common markers of growth: weight-for-age, weight-for-height, and height-for-age Z -scores. On the basis of these undernutrition exposures, we applied a counterfactual approach to quantify the relative risk of infectious disease (subsequent diarrhoea, lower respiratory infection, and measles) and protein energy malnutrition morbidity and mortality per day of diarrhoea and quantified the burden of diarrhoeal disease due to these outcomes caused by undernutrition. Findings: Diarrhoea episodes are significantly associated with childhood growth faltering. We found that each day of diarrhoea was associated with height-for-age Z -score (–0·0033 [95% CI −0·0024 to −0·0041]; p=4·43 × 10 −14 ), weight-for-age Z -score (–0·0077 [–0·0058 to −0·0097]; p=3·19 × 10 −15 ), and weight-for-height Z -score (–0·0096 [–0·0067 to −0·0125]; p=7·78 × 10 −11 ). After addition of the DALYs due to the long-term sequelae as a consequence of undernutrition, the burden of diarrhoeal diseases increased by 39·0% (95% uncertainty interval [UI] 33·0–46·6) and was responsible for 55 778 000 DALYs (95% UI 49 125 400–62 396 200) among children younger than 5 years in 2016. Among the 15 652 300 DALYs (95% UI 12 951 300–18 806 100) associated with undernutrition due to diarrhoeal episodes, more than 84·7% are due to increased risk of infectious disease, whereas the remaining 15·3% of long-term DALYs are due to increased prevalence of protein energy malnutrition. The burden of diarrhoea has decreased substantially since 1990, but progress has been greater in long-term (78·7% reduction [95% UI 69·3–85·5]) than in acute (70·4% reduction [95% UI 61·7–76·5]) DALYs. Interpretation: Diarrhoea represents an even larger burden of disease than was estimated in the Global Burden of Disease Study. In order to adequately address the burden of its long-term sequelae, a renewed emphasis on controlling the risk of diarrhoea incidence may be required. This renewed effort can help further prevent the potential lifelong cost on child health, growth, and overall potential. Funding: Bill & Melinda Gates Foundation.